2019 IEEE 6th Portuguese Meeting on Bioengineering (ENBENG) 2019
DOI: 10.1109/enbeng.2019.8692527
|View full text |Cite
|
Sign up to set email alerts
|

Detection and adsorption of Triclosan on sensors based on PAH/PVS thin-films

Abstract: Given the vital role of water in life it is paramount to thrive and succeed in areas that look to clean and prevent further contamination in water bodies. Triclosan (TCS) is present in most of our day-today products and if left unchecked it can lead to long-term significant problems due to its many inauspicious effects in both human and animal health. Thus arose the need to develop sensors to detect and possibly remove TCS for aqueous solutions. This work was rooted on this premise and sensors based on LbL pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To the best of the authors' knowledge, this type of study has not yet been conducted, with regard to an analysis of how LbL thin films behave when subjected to different applied voltages, while detecting PPCP or EDC such as in this case with EE2. However, the need to perform this experiment arose from the lack of information regarding this subject while conducting experimental works within our research group that are directly related to both this kind of sensor, (LbL films on IDE) and emerging compounds such as triclosan and EE2 [20][21][22][23]. This type of film ([PEI/PSS] 5 ) was chosen since it is viable, as demonstrated in previous works conducted where several types of thin film combinations were studied to ascertain which one (or ones) would be the most suitable to use in experiments that aim to detect (and possibly monitor) noxious compounds in water bodies [14].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors' knowledge, this type of study has not yet been conducted, with regard to an analysis of how LbL thin films behave when subjected to different applied voltages, while detecting PPCP or EDC such as in this case with EE2. However, the need to perform this experiment arose from the lack of information regarding this subject while conducting experimental works within our research group that are directly related to both this kind of sensor, (LbL films on IDE) and emerging compounds such as triclosan and EE2 [20][21][22][23]. This type of film ([PEI/PSS] 5 ) was chosen since it is viable, as demonstrated in previous works conducted where several types of thin film combinations were studied to ascertain which one (or ones) would be the most suitable to use in experiments that aim to detect (and possibly monitor) noxious compounds in water bodies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the characterization of aqueous environmental matrices is performed by analyzing the electrical impedance components (reactance, resistance, capacitance, and loss tangent) as a function of frequency signals applied to nanostructures adsorbed onto solid substrates with interdigitated electrodes [37]. It has been reported that the TCS adsorbed amount per unit of area on thin-films is reduced if the outer layers have negative charged polyelectrolyte [43]. The stability of the sensorial layers produced by the LbL technique is dependent of the solution's pH and the degree of ionization of the uppermost polyelectrolyte layer [44].…”
Section: Introductionmentioning
confidence: 99%